THE QURAN'S PERSPECTIVE AND COVID-19 IN INDONESIA - Muhammad Reza Fadil; Desi Ayuni Sari; Rendy Sanjaya; Mutia Sari (Universitas Muhammadiyah Surakarta, 2022)
The Covid-19 pandemic is a serious disease that spreading to the world community. In Indonesia, Covid-19 causes health and social problems. This paper examines how the spread of Covid-19 in Indonesia, how Islamic scholars and scientists in Indonesia view the Covid-19 problem, and how the Qur'an provides solutions in dealing with Covid-19. This study uses the thematic interpretation method with a conceptual analysis approach in unraveling research problems. The results show that the spread of Covid-19 in Indonesia is relatively high among countries in the world, the views of clergy and scientists in Indonesia about Covid-19 are not always in line, and the Qur'an contains teachings in the form of efforts to mitigate the spread of the virus by teaching habits of maintain body hygiene, consuming nutritions, multiply zikr to gain relaxing of mind, and be smart toward receiving information about Covid-19.